The Effect Of Counseling About Breast milk Supplementary Foods (Carrots, Radish, Quail Eggs) on Increasing Knowledge And Attitudes Of Mothers in Posyandu Melati A and B, in Kamarora Village, Nokilalaki District : Breast Milk Supplement Foods - Ni Ketut Kariani; Endang Sri Mulyawati L; Firnasrudin Rahim (Politeknik Karya Persada Muna, 2021)
Background : Complementary Foods ASI (MP-ASI) is a reliable tool to build quality human resources, because MP-ASI is one of the foods that guarantees baby's growth and development. The purpose to increase knowledge and attitudes of mothers in Posyandu Melati A and B, Kamarora Village, Nokilalaki District Method: This study uses a quantitative research with a quasi-experimental design with a pre-experimental one-group pre-post-test design. The sample is 48 people with total sampling technique. Data analysis using Wilcoxon test Results: The result of knowledge before counseling was sufficient amounting to 23 respondents (47.9%) after counseling was good 41 respondents (85.4%) attitude before counseling did not accept 47 respondents (97.9%) after counseling received attitude amounted to 34 respondents (70.8%) Conclusions: there is an extension influence about the provision of breast milk companion food (Carrots, Radish, Quail Eggs) to increase maternal knowledge and attitude in Posyandu Melati A and B Kamarora Kec.Nokilalaki Village.with a p-value of 0.000, < (α0.5) Keywords: Complementary feeding of breast milk (Carrots, Radish, Quail Eggs), Increased knowledge, Attitude